FLOWERING LOCUS T2 regulates spike development and fertility in temperate cereals. (5th October 2018) - Shaw, Lindsay M; Lyu, Bo; Turner, Rebecca; Li, Chengxia; Chen, Fengjuan; Han, Xiuli; Fu, Daolin; Dubcovsky, Jorge
Abstract : FLOWERING LOCUS T2 ( FT2 ) is expressed in the distal part of the developing wheat spike and contributes to the regulation of the number of spikelets per spike. Abstract: FLOWERING LOCUS T2 ( FT2 ) is the closest paralog of the FT1 flowering gene in the temperate grasses. Here we show that overexpression of FT2 in Brachypodium distachyon and barley results in precocious flowering and reduced spikelet number, while down-regulation by RNA interference results in delayed flowering and a reduced percentage of filled florets. Similarly, truncation mutations of FT2 homeologs in tetraploid wheat delayed flowering (2–4 d) and reduced fertility. The wheat ft2 mutants also showed a significant increase in the number of spikelets per spike, with a longer spike development period potentially contributing to the delayed heading time. In the wheat leaves, FT2 was expressed later than FT1, suggesting a relatively smaller role for FT2 in the initiation of the reproductive phase. FT2 transcripts were detected in the shoot apical meristem and increased during early spike development. Transversal sections of the developing spike showed the highest FT2 transcript levels in the distal part, where new spikelets are formed. Our results suggest that, in wheat, FT2 plays an important role in spike development and fertility and a limited role in the timing of the transition between the vegetative and reproductive shoot apical meristem.